An Error Analysis Made by the English Department Students in Translating Tourism Brochure - Walanda, Anisa Erda; Ardi, Havid (Universitas Negeri Padang, 2024)
This study aims at finding out the types of errors made by the English Department students of Universitas Negeri Padang in translating tourism brochure from Bahasa Indonesia into English. This study used a descriptive qualitative method. The data were the translation of tourism brochures of the entitled “Lembah Harau, Indahnya Minangkabau” and “Destinasi Wisata Alam yang Masih Alami di Sumatera Barat” done by English Department students of Universitas Negeri Padang who have taken Indonesia English Translation Subject. The data were collected using a test and were analyzed using the error analysis. The results of the study indicate that there are four types of errors which error of devition of meaning is the most error frequently committed by the students in their translation with the frequency of 180 times (63,15%). Omission of meaning (26.66%) is the second, while the error of addition and the error of invention of meaning are the least error found in the students’ translation.